2019
DOI: 10.5194/acp-2019-679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adding value to Extended-range Forecasts in Northern Europe by Statistical Post-processing Using Stratospheric Observations

Abstract: Abstract. The skill scores of the Extended-Range Forecasts (ERF) of the European Centre for Medium-Range Weather Forecasts (ECMWF) are still quite modest for the forecast weeks 3–6 in Northern Europe. As there are known stratospheric precursors impacting the surface weather with potential to improve ERFs, we aim to quantify the effect of these predictors and post-process the ERFs with them. During boreal winter the quasi-biennial oscillation (QBO) affects the stratospheric polar vortex; the easterly (westerly)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Moreover, the lid of several atmospheric model products has been raised into the mesosphere (Polavarapu et al, 2005) and it has been demonstrated that this can improve numerical weather and climate models (Orsolini et al, 2011;Charlton-Perez et al, 2013;Kidston et al, 2015). But the full potential of high-top models can only be unlocked if middle atmospheric winds are better represented (Baker et al, 2014;Korhonen et al, 2019;Lee et al, 2019). Hence, it is timely to explore novel datasets and assimilation approaches that can constrain the upper-stratospheric dynamics in atmospheric model products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lid of several atmospheric model products has been raised into the mesosphere (Polavarapu et al, 2005) and it has been demonstrated that this can improve numerical weather and climate models (Orsolini et al, 2011;Charlton-Perez et al, 2013;Kidston et al, 2015). But the full potential of high-top models can only be unlocked if middle atmospheric winds are better represented (Baker et al, 2014;Korhonen et al, 2019;Lee et al, 2019). Hence, it is timely to explore novel datasets and assimilation approaches that can constrain the upper-stratospheric dynamics in atmospheric model products.…”
Section: Introductionmentioning
confidence: 99%
“…The data of Figs. 1-6 are available at https://fmi.b2share.csc.fi/records/8ceb3da6ce144180b5304ad080af88af (Korhonen, 2024).…”
Section: Data Availabilitymentioning
confidence: 99%
“…However, the observational coverage of these two layers is nowhere near as dense as that of the troposphere. Some of the largest uncertainties in current reanalyses occur in these levels, leading the wind representation of mesospheric winds to lag behind other areas (Baker et al, 2014;Korhonen et al, 2019). For instance, Duruisseau et al (2017) compared high-altitude (pressure less than 20 hPa) ERA-Interim values against wind measurements taken from a balloon radiosonde and noted that the standard deviations of the differences were greater than 5 m⋅s −1 in some cases.…”
Section: Introductionmentioning
confidence: 99%